2018
DOI: 10.1080/0092623x.2018.1437579
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Impact of the Commonly Used Female Contraceptive Methods in Egypt on Female Sexual Function

Abstract: Temporary methods of female contraception are commonly practiced in Egypt, but an increased total fertility rate was recently reported. Impaired female sexual function (FSF) due to contraceptive use can be a reason for irregular use/discontinuation. This study aimed at identifying the type(s) of the commonly used contraceptive method(s) in Egypt that can impair FSF. The sexual function of women on some form of temporary contraceptive was compared to that of women not using contraceptives. All participants answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…When asked about their subjective opinions on the influence of hormonal contraceptives, women declared no effect or a slight decrease in sexual response, which is in line with some previous observations -no effect in 55% of users [30].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…When asked about their subjective opinions on the influence of hormonal contraceptives, women declared no effect or a slight decrease in sexual response, which is in line with some previous observations -no effect in 55% of users [30].…”
Section: Discussionsupporting
confidence: 88%
“…Third, we did not evaluate the effect of progestin-only pills (POP), hormonal IUDs, patches, rings or injections. In the Hassanin et al study, 95% and 84% of injectable contraceptive and POP users reported a decline in sexual function [ 30 ]. Finally, a prospective study with a sexual function evaluation before and after using hormonal contraceptives would be more reliable in showing a causative association.…”
Section: Discussionmentioning
confidence: 99%
“…However, the population induced in the study was small to draw the de nite conclusion. Some differences might be also due to cultural script and ethnicity -women from Europe seems to have higher prevalence of pain during intercourse when using hormonal contraceptives compared to other continents (20) When asked about subjective opinion on the in uence of hormonal contraceptives women declared no effect or slightly decrease in sexual response, what is in line with some previous observation -no effect in 55% of users (29).…”
Section: Discussionsupporting
confidence: 76%
“…Secondly, propensity for inhibition/excitation could also be evaluated, what is currently being pain more and more attention (22). Thirdly, we have not evaluated the effect of progestin-only pills (POP), hormonal IUD, patches, ringd and injections, like in Hassanin et al study where 95% and 84% of injectable contraceptive and POP users reported decline in sexual function (29). Finally, a prospective character of the study with sexual function evaluation before introducing the hormonal contraceptive would be more reliable in showing the association.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, for example, researchers found that HC type moderated women's experience of sexual side effects. In particular, they found that women using combined OCs exhibited no impairment in sexual functioning from HC use, while women using progestin-only injectables and progestin only pills did (Hassanin et al, 2018). Given the important role of estradiol in NC women's sexual desire (Roney & Simmons 2013;2016;Shirazi et al, 2019), it is unsurprising that progestin only methods of HCs are associated with decreased sexual functioning.…”
Section: Prescription-based Factorsmentioning
confidence: 99%